2010
DOI: 10.1371/journal.ppat.1000969
|View full text |Cite
|
Sign up to set email alerts
|

An Outer Membrane Receptor of Neisseria meningitidis Involved in Zinc Acquisition with Vaccine Potential

Abstract: Since the concentration of free iron in the human host is low, efficient iron-acquisition mechanisms constitute important virulence factors for pathogenic bacteria. In Gram-negative bacteria, TonB-dependent outer membrane receptors are implicated in iron acquisition. It is far less clear how other metals that are also scarce in the human host are transported across the bacterial outer membrane. With the aim of identifying novel vaccine candidates, we characterized in this study a hitherto unknown receptor in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
154
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(162 citation statements)
references
References 43 publications
7
154
0
1
Order By: Relevance
“…TonB-dependent receptors from several pathogens are known to be immunogenic and, in some cases, immunoprotective. For example, immunoproteomic analysis of the whole cell proteins of Riemerella antipestifer revealed that TonB-dependent receptor was among the immunogenic outer membrane proteins (Q. , and a study with a Znuptake Tdr, ZnuD, of Neisseria meningitidis showed that it could induce bactericidal antibodies upon immunization of mice (Stork et al 2010). Similarly, Tdr with vaccine potentials have been found in Haemophilus ducreyi and, as reported by us, P. fluorescens (Afonina et al 2006, Fusco et al 2010, Leduc et al 2011, Y. Hu et al 2012.…”
Section: Discussionsupporting
confidence: 58%
“…TonB-dependent receptors from several pathogens are known to be immunogenic and, in some cases, immunoprotective. For example, immunoproteomic analysis of the whole cell proteins of Riemerella antipestifer revealed that TonB-dependent receptor was among the immunogenic outer membrane proteins (Q. , and a study with a Znuptake Tdr, ZnuD, of Neisseria meningitidis showed that it could induce bactericidal antibodies upon immunization of mice (Stork et al 2010). Similarly, Tdr with vaccine potentials have been found in Haemophilus ducreyi and, as reported by us, P. fluorescens (Afonina et al 2006, Fusco et al 2010, Leduc et al 2011, Y. Hu et al 2012.…”
Section: Discussionsupporting
confidence: 58%
“…Two genes, alr3242 and alr4028-4029 (the latter is a single ORF mistakenly annotated as two independent genes [43]), encoding putative TBDRs regulated by Zur in Anabaena are described here. alr3242 is highly induced (ϳ100-fold) and reaches a high level of expression in the zur mutant, suggesting that Alr3242 is probably a TBDR specific for the import of zinc complexes from the outer medium, which hitherto has been described only for human pathogens (58). The alr4028-4029 gene is also induced in the zur mutant but to a lower extent (ϳ10-fold) ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Transport by TBDRs of iron complexes (siderophores, heme, and ferritin) and vitamin B 12 (cobalamin) is well characterized (44). However, the involvement of the TBDR in the import of divalent metals other than iron was not reported until very recently (29,51,58). Twenty-two genes in the Anabaena genome encode putative TBDRs (43), suggesting that some of them may be involved in the transport of molecules other than iron complexes or vitamin B 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of uptake for ferric-siderophore complexes by a TBDT has been described in detail in the E. coli model system (Chakraborty et al 2007). Most TBDT-like proteins are known to transport iron compounds (siderophores or heme) or cobalamine (Noinaj et al 2010); recent reports, however, indicate that these kind of receptors are also involved in the uptake of nickel (Schauer et al 2007) and zinc (Stork et al 2010). …”
Section: Transporters For Metal Uptake Through the Outer Membranementioning
confidence: 99%